Calculations of theoretical efficiencies for electrochemically-mediated tandem solar water splitting as a function of bandgap energies and redox shuttle potential. Issue 1 (19th November 2018) - Keene, Sam; Bala Chandran, Rohini; Ardo, Shane
Abstract : Tandem Z-scheme solar water splitting devices composed of two light-absorbers that are connected electrochemically by a soluble redox shuttle constitute a promising technology for cost-effective solar hydrogen production. Abstract : Tandem Z-scheme solar water splitting devices composed of two light-absorbers that are connected electrochemically by a soluble redox shuttle constitute a promising technology for cost-effective solar hydrogen production. Herein, efficiency limits of these devices are modeled by combining the detailed-balance model of the light-absorbers with Butler–Volmer electron-transfer kinetics. The impacts of the redox shuttle thermodynamic potential, light-absorber bandgaps, and electrocatalytic parameters on the solar-to-hydrogen conversion (STH) efficiency are modeled. We report that the thermodynamic potential of the redox shuttle with respect to the hydrogen and oxygen evolution potentials has a direct effect on both the STH efficiency and the optimal tandem light-absorber bandgaps needed to achieve the maximum possible STH efficiency. At 1 sun illumination and assuming ideal and optimally selective electrocatalytic parameters, the STH efficiency varies from a minimum of 21%, for a redox shuttle potential of 0 V vs. the reversible hydrogen electrode (RHE), to a maximum of 34%, for a redox shuttle potential of either 0.36 V or 1.06 V vs. RHE. To attain the maximum possible STH efficiency of 34%, the light-absorber bandgaps must be 1.53 eV and 0.75 eV, yet the optimal redox shuttle potential depends on whether the hydrogen-evolving or oxygen-evolving light-absorber has the larger bandgap. Results also underscore the importance of optimizing the absorptance of the top light-absorber, which enables large STH efficiencies to be achieved with a wider range of bandgap combinations. Moreover, given the large overpotentials for the oxygen evolution reaction and reasonably low overpotentials for most redox shuttle reactions, the tandem design is more efficient than a single light-absorber design even when the potential of the redox shuttle exceeds 1.23 V vs. RHE. When the exchange current density of the redox shuttle reactions is as low as 10 −5 mA cm −2, STH efficiencies as large as 22% are still achievable as long as selective catalysis and optimal redox shuttle potential are assumed, suggesting that even slow redox shuttle reactions may not limit the practicality of these devices.